2008
DOI: 10.1080/01421590802043827
|View full text |Cite
|
Sign up to set email alerts
|

Patients consulting with students in general practice: Survey of patients’ satisfaction and their role in teaching

Abstract: Patients in general practice have a positive view towards consulting with senior students. Even unprepared patients see themselves as contributors to teaching, and their capacity in this respect is probably under-utilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
66
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 20 publications
14
66
0
Order By: Relevance
“…(Cooke et al 1996;O' Flynn et al 1997;Bentham et al 1999;Devera-Sales et al 1999;Chipp et al 2004;Salisbury et al 2004;Choudhury et al 2006;Haffling & Hakansson 2008;Hudson et al 2010). Closer questioning revealed that for between a quarter to half of the patients giving permission depended on the complaint type (O' Flynn et al 1997;Salisbury et al 2004;Haffling & Hakansson 2008).…”
Section: Consent To Student Participationmentioning
confidence: 92%
“…(Cooke et al 1996;O' Flynn et al 1997;Bentham et al 1999;Devera-Sales et al 1999;Chipp et al 2004;Salisbury et al 2004;Choudhury et al 2006;Haffling & Hakansson 2008;Hudson et al 2010). Closer questioning revealed that for between a quarter to half of the patients giving permission depended on the complaint type (O' Flynn et al 1997;Salisbury et al 2004;Haffling & Hakansson 2008).…”
Section: Consent To Student Participationmentioning
confidence: 92%
“…2 Males may be less self-conscious than females, not caring much whether students are present or not. A recent study 7 reported that over 90% of patients were satisfied with con- sultations conducted by medical students and that most would consult with a student again. However, emotional problems and intimate examinations were matters for concern.…”
Section: Discussionmentioning
confidence: 99%
“…Prior knowledge of medical student interactions and the method of obtaining consent influence patients' willingness to accept a student as part of their care. [5][6][7] Studies of student involvement in specialties, in general practice and in ambulatory clinics all showed a positive patient response to student involvement. 4,5,8,9 This acceptance decreases with increasing intimacy of patient consultation.…”
Section: Introductionmentioning
confidence: 96%